A Perspective on Future Tiger Shark Research - Holland, Kim N.; Anderson, James M.; Coffey, Daniel M.; Holmes, Bonnie J.; Meyer, Carl G.; Royer, Mark A. (Frontiers in Marine Science, 2019)
This ‘Perspectives’ paper identifies aspects of tiger shark (Galeocerdo cuvier) biology that are currently unknown or for which additional data are needed to improve interpretive power. Some of these data gaps may be regional. Technical or methodological approaches to acquiring these data are suggested. Some of these technologies already exist, some are in development and some exist in concept only. Reproductive biology and behavior, social interactions and the behavioral ecology of sub-adults are among the areas identified as deserving of future research effort